Upgrading the e-AgriMet app to an integrated mobile-based climate and crop pest information system - Agali, Alhassane; Quenum, Narcisse; Maiga, Idrissa; Ali, Abdou; Mohamed, Hamatan; Gadédjisso-Tossou, Agossou; Houngnibo, Mandela C.; Segnon, Alcade C; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
There is big interest of having an integrated system for disseminating and communicating climate and pest information for early warning and decision making. AGRHYMET RCC/WAS e-AgriMet mobile Application, initially dedicated to Agro-Hydro-Climatic information dissemination, could also integrate other key risks that impact agriculture in the West Africa region, such as crop pest and diseases. The e-AgriMet Application is an open source development tool that can integrate other aspects or additional modules. The AICCRA projects offer an opportunity to work on integrating phytosanitary aspects and solving other gaps of the e-AgriMet mobile application by capitalizing existing achievements.